Development of biodegradable composite micro-perforated panel made from natural fibre composites with evaluation of its acoustic and mechanical properties - Chin, Desmond Daniel Vui Sheng (2020)
Micro-perforated panel (MPP) has been widely considered as a promising alternative for sound absorption purposes. Plenty of research has been done to improve the sound absorption of MPP but no specific work highlights the material structure effect towards its sound absorption performance. MPP is mostly made from metallic or plastic materials which does not exhibits any pores or tortuous structure and therefore, material structure issue is often being eliminated from analysis. In order to study the material structure effect, alternative material must be used to fabricate MPP. Numerous research found that natural fibre possesses excellent sound absorption properties due to its porous and tortuous structure. Yet, natural fibre has low tolerance towards mechanical processing and thus binder must be incorporated to overcome this shortcoming. This thesis basically describes the development process of biodegradable composite micro-perforated panel (BC-MPP) made from natural fibre (kenaf, wood, and coconut) and polylactic acid (PLA) composites. BC-MPP samples were fabricated with different material composition percentage of natural fibre and PLA. The effect of material composition percentage, perforation ratio, perforation diameter, and air cavity thickness were investigated. The effect of material structure towards the sound absorption performance of BC-MPP sample was studied. It has been found that existence of pores and tortuous structure can indeed influence the sound absorption performance of BC-MPP sample. The sound absorption performance of BC-MPP sample was compared to conventional MPP and it has been found that BC-MPP possessed better sound absorption performance courtesy to its porous and tortuous structure. BC-MPP sample also possessed better tensile strength compared to common sound absorption panel such as medium density fibreboard, hardboard, commercial ceiling board, and plywood.